Process evaluation of a medical assistant health coaching intervention for type 2 diabetes in diverse primary care settings. Issue 2 (17th November 2021) - Clark, Taylor L; Fortmann, Addie L; Philis-Tsimikas, Athena; Bodenheimer, Thomas; Savin, Kimberly L; Sandoval, Haley; Bravin, Julia I; Gallo, Linda C
Abstract: Team-based models that use medical assistants (MAs) to provide self-management support for adults with type 2 diabetes (T2D) have not been pragmatically tested in diverse samples. This cluster-randomized controlled trial compares MA health coaching with usual care in adults with T2D and poor clinical control ("MAC Trial"). The purpose was to conduct a multi-method process evaluation of the MAC Trial using the Reach, Effectiveness, Adoption, Implementation, and Maintenance framework. Reach was assessed by calculating the proportion of enrolled participants out of the eligible pool and examining representativeness of those enrolled. Key informant interviews documented adoption by MA Health Coaches. We examined implementation from the research and patient perspectives by evaluating protocol adherence and the Patient Perceptions of Chronic Illness Care (PACIC-SF) measure, respectively. Findings indicate that the MAC Trial was efficient and effective in reaching patients who were representative of the target population. The acceptance rate among those approached for health coaching was high (87%). Both MA Health Coaches reported high satisfaction with the program and high levels of confidence in their role. The intervention was well-implemented, as evidenced by the protocol adherence rate of 79%; however, statistically significant changes in PACIC-SF scores were not observed. Overall, if found to be effective in improving clinical and patient-reported outcomes, the MAC model holds potential for wider-scale implementation given its successful adoption and implementation and demonstrated ability to reach patients with poorly controlled T2D who are at-risk for diabetes complications in diverse primary care settings. Abstract : A medical assistant health coaching intervention for adults with type 2 diabetes was effective in reaching many patients, was well-accepted, and was delivered as intended.